2003
DOI: 10.1007/s00442-003-1349-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal colonization mediated by species interactions in arctic tundra

Abstract: The Alaskan tussock tundra is a strongly nutrient-limited ecosystem, where almost all vascular plant species are mycorrhizal. We established a long-term removal experiment to document effects of arctic plant species on ecto- and ericoid mycorrhizal fungi and to investigate whether species interactions and/or nutrient availability affect mycorrhizal colonization. The treatments applied were removal of Betula nana ( Betulaceae, dominant deciduous shrub species), removal of Ledum palustre ( Ericaceae, dominant ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
4
29
3
4
Order By: Relevance
“…Responses to environmental changes in these microbial groups are important, because mycorrhizal fungi supply the host plants with nutrients from the soil in exchange for labile C from the plant, and because fungal composition and diversity influences plant productivity, stability and diversity. In the Subarctic and Low Arctic, most studies of fungal responses to warming and nutrient addition or plant species interactions (Urcelay et al 2003) have focused on ectomycorrhizal fungi, because many of these fungi easily can be distinguished morphologically and because they colonize roots of widespread arctic shrubs species as dwarf birch (Betula nana) and willows (Salix spp). For instance, the ectomycorrhizal community on roots of the prostrate willow (Salix herbacea x polaris) at an arctic-alpine fellfield consists of at least seven fungal species, of which some may also be found in boreal forests.…”
Section: Mycorrhizal Fungi: Function Interactions With Host Plants mentioning
confidence: 99%
“…Responses to environmental changes in these microbial groups are important, because mycorrhizal fungi supply the host plants with nutrients from the soil in exchange for labile C from the plant, and because fungal composition and diversity influences plant productivity, stability and diversity. In the Subarctic and Low Arctic, most studies of fungal responses to warming and nutrient addition or plant species interactions (Urcelay et al 2003) have focused on ectomycorrhizal fungi, because many of these fungi easily can be distinguished morphologically and because they colonize roots of widespread arctic shrubs species as dwarf birch (Betula nana) and willows (Salix spp). For instance, the ectomycorrhizal community on roots of the prostrate willow (Salix herbacea x polaris) at an arctic-alpine fellfield consists of at least seven fungal species, of which some may also be found in boreal forests.…”
Section: Mycorrhizal Fungi: Function Interactions With Host Plants mentioning
confidence: 99%
“…Increased soil temperature can influence root growth, phenology and architecture, respiration and ion uptake, water and nutrient availability , but the impacts on soil microbial communities is varied and often unpredictable (Zak et al, 2000). Responses of mycorrhizal fungi to simulated global change factors (CO 2 , warming, shading and fertilization) are also variable, although several studies have found a not unexpected link between increased plant C allocation belowground and increased mycorrhizal colonization (Staddon et al, 2002;Urcelay et al, 2003;Fitter et al, 2004;Heinemeyer and Fitter, 2004;Olsrud et al, 2004;. Some studies have found that experimental treatments alter mycorrhizal community composition (Rygiewicz et al, 2000;Parrent et al, 2006), but these changes are rarely of sufficient magnitude to significantly change the overall richness or diversity of the community.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados correspondientes a los ensayos de germinación, para el total de especies típicas de cada fisonomía, se analizaron mediante Análisis de la varianza (Anova) con rangos (no paramétrico), puesto que la variable porcentaje de germinación, en cada situación experimental, no cumplió con los supuestos de normalidad ni homogeneidad de varianzas (Conover & Iman 1981, Hora & Conover 1984, Zar 1999, Urcelay et al 2003, aun cuando los porcentajes fueron transformados en √arco-seno. Este Anova con rangos fue tri-factorial, considerando a la fisonomía, la temperatura y la luz/oscuridad como los tres factores principales.…”
Section: Experimento De Germinaciónunclassified
“…Se aplicó un LDS de Fischer como test a posteriori. La interpretación de los resultados que arroja este tipo de análisis, se realiza de la misma manera que para un Anova paramétrico (Zar 1999, Urcelay et al 2003.…”
Section: Experimento De Germinaciónunclassified